Comparative Effectiveness of Three Ovarian Hyperstimulation Protocol in In Vitro Fertilization (IVF) Cycles for Women with Polycystic Ovary Syndrome - Chen, Yilu (Med Sci Monit, 2018)
BACKGROUND: The aim of this study was to evaluate the efficacy of specific in vitro fertilization (IVF) protocols for patients with polycystic ovary syndrome (PCOS), and therefore, analyze the first-rank intention IVF protocol. MATERIAL/METHODS: In this study, 408 PCOS patients (464 treatment cycles) were enrolled and assigned to one of 3 groups: group 1 [oral contraceptive long-term regimen group (OC-L protocol group, n=91)], group 2 (GnRH antagonist protocol, n=80), and group 3 [follicular phase long-term regimen group, C(1)-L protocol group n=293]. The endpoints are the number of eggs, oocyte maturation rate, high-quality embryo rate and clinical pregnancy rate after fresh embryos transfer, the incidence of ovarian hyperstimulation syndrome and abortion rate. RESULTS: The number of eggs, oocyte maturation rate, and high-quality embryo rate in the C(1)-L protocol group were significantly higher than those in the other 2 groups. The fertilization rate and cleavage rate of the 3 groups were not significantly different. After fresh embryo transplantation, the pregnancy rate of C(1)-L protocol group was significantly higher than that of the other groups. CONCLUSIONS: This study showed that the super-long downregulation in follicular phase regimen has advantages of simple treatment process, high oocyte maturation rate, high quality embryo rate, and pregnancy rate. It is a good choice for PCOS patients to promote ovulation during IVF.